Failure to connect how computers affect our children's minds, for better and worse - Healy, Jane M. (Simon & Schuster, 1998)
Publisher's description: Failure to Connect sounds a wake-up call for teachers and parents who believe that computers alone will solve our educational problems. The bottom line: Adult attention rather than gigabytes is what makes children grow.
Keywords: Enseignement assisté par ordinateur; Ordinateurs et enfants; Computer-assisted instruction; Computers and children; Kind; Computer